The Increasing Intention Of Tourist Loyalty Through Geopark Destination Attributes (The Research of Ciletuh-Palabuhanratu Geopark Visitors) - et. al., Riski Taufik Hidayah, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The tourism industry was the sector most affected during the Covid19 pandemic, which had consequences for the economic downturn. Data estimates that 15 million tourism workers have the potential to lose their livelihoods by the end of 2020. So action to restore the tourism industry needs to be taken immediately. Efforts to restore, develop and improve tourist destinations can be carried out by conducting studies on tourist loyalty which can be influenced by destination attributes. The most important destination attribute at this time is the application of health protocols in tourist areas by all interested parties. The purpose of this research is to determine the influence that the destination attributes contribute to the loyalty intentions of tourists. The method used in this research is verification with the population, namely tourists who have visited the Ciletuh-Pelabuhanratu Geopark at least once and wishing to make visits in the future. The analytical method used is the Spearman rank correlation, the coefficient of determination, and the t test with a significance level of five percent. This study found that the destination attribute gave an influence of 40.84% ​​on the loyalty intentions of tourists.